Management of Foot and Root Rot Disease of Eggplant (Solanum melongena L.) Caused by Sclerotium rolfsii under In Vivo Condition (The Agriculturists, 2018)
An experiment was conducted to evaluate the efficacy of fungicides, plant extracts, organic manure and biocontrol-agents against foot and root rot disease of eggplant caused by Sclerotium rolfsii. Five chemical fungicides, two plant extracts, organic amendment - poultry manure and biocontrol-agent Trichoderma harzianum were evaluated against the disease in field condition. Fungicides and plant extracts were sprayed at the base of each plant and adjacent soil at 40, 50 and 60 days after transplanting. Organic manure and biocontrol-agent were applied to the soil before transplanting. The lowest disease incidence (7.10 %) and no disease severity were observed in Bavistin 50 WP at 120 DAT followed by Topgan 50 WP and Ridomil Gold. Higher yield and plant growth like plant hight (88 cm), number of branch/plant (7.33) and number of leaf/branch (25.33) was also supported by Bavistin 50 WP . The highest benefit cost ratio was also calculated in Bavistin 50 WP followed by Topgan 50 WP and Ridomil Gold. Application of biocontrol-agent (T. harzianum) also showed promising effect against foot and root rot disease.The Agriculturists 2018; 16(1) 78-86